Cellulose nanofibrils/polyvinyl alcohol/silver nanoparticles composite hydrogel: Preparation and its catalyst degradation performance of cationic dye. Issue 22 (10th February 2022) - Li, Yuhang; Luan, Yunhao; Liu, Wanyi; Wang, Cong; Cao, Hui; Liu, Pengtao
Abstract: Metal nanoparticles play an essential role in catalyzing the degradation of dyes in industrial wastewater. In order to improve the catalytic reduction and discoloration performance of silver nanoparticles (Ag NPs) to cationic dyes and facilitate recovery, we report an improved method to prepare cellulose nanofibrils/polyvinyl alcohol (CNF/PVA) porous composite hydrogel and use it to support metal nanoparticles. Silver ions were reduced to Ag NPs by the in situ reduction method after being adsorbed on the surface of the hydrogel by electrostatic adsorption, and the maximum adsorption capacity was about 136.4 mg/g. The obtained CNF/PVA/Ag NPs (CPA) composite hydrogel was characterized by scanning electron microscope, transmission electron microscopy, Fourier transform infrared spectroscopy, X‐ray diffraction, and energy dispersive spectroscopy. Furthermore, we demonstrate the efficient utilization of composite hydrogel as a container in the discoloration of methylene blue (cationic dye) and methyl orange (cationic dye) in the presence of NaBH4 . The hydrogel was quickly recovered and reused without a decrease in activity for five cycles. It showed fantastic potential in water resources protection and catalytic application. Abstract :